(untitled) (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2024)
The term "Digital Dictionary" refers to an electronic or online resource that provides definitions, translations, pronunciations, and other linguistic information about words and phrases. Unlike traditional print dictionaries, digital dictionaries offer enhanced features such as search functionality, audio pronunciations, and multimedia content. They can be accessed via websites, mobile applications, or software programs, making them convenient tools for language learners, writers, and researchers. Digital dictionaries often include additional resources such as synonyms, antonyms, example sentences, and usage notes, enriching the user’s understanding of language. Many digital dictionaries are continuously updated to reflect changes in language usage, slang, and new words. Some platforms also incorporate user- generated content, allowing for collaborative contributions that enhance the richness of the resource. The rise of digital dictionaries has transformed how people engage with language, facilitating easier access to information and supporting diverse learning styles. They play a crucial role in education and communication in an increasingly interconnected world